Situation Report: Romania, 11 July 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Manescu Speech to Comecon Council Reflects Romanian Concerns Romania's Position at the Security Conference Talks in Geneva Romanian Protests Its Exclusion from UN Charter Committee Parliamentary Delegation Visits Turkey New Interpretations of Antonescu and World War II Large Areas in Romania Affected by Floods Financial Control and Economic Efficiency Protecting the Cultural Patrimony